The kinetics and dynamics of cyfluthrin excretion from the body of cattle after treatment flayblok - S. V. Engashev; D. D. Novikov; A. N. Tokarev; S. V. Rusakov (Российский паразитологический журнал, 2016)
The results indicate that the use of the drug flayblok residues of cyfluthrin in plasma, milk, organs and tissues are not found in any one of the selection date. The concentration of residual cyfluthrin below the detection limit of the method. Consequently, livestock products after treatment flayblok can be used without restriction.